“Using Folk Applied Arts to Foster Creativity and Cultural Awareness in Children” - Raxmonova Rayxon Zoir qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article explores the role of folk applied arts in enhancing creativity, aesthetic skills, and cultural awareness in school-age children. By engaging in activities such as designing traditional patterns, creating ornaments, and experimenting with colors and textures, children develop cognitive, social, and emotional skills. The study highlights that integrating folk arts into the curriculum promotes creative thinking, cultural appreciation, and social interaction, providing a comprehensive approach to holistic child development.